Fly ash-slag-based recycled aggregate sea sand geopolymer concrete and preparation method thereof

By using fly ash-slag-based recycled aggregate and sea sand combined with geopolymer concrete technology, the problems of high energy consumption and high carbon emissions in concrete production and shortage of river sand resources are solved, and efficient and environmentally friendly concrete production is achieved.

CN119490325APending Publication Date: 2025-02-21GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311041297.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

There are problems of high energy consumption and high carbon emissions in the existing concrete production process, and the shortage of river sand resources has led to environmental pollution and resource depletion.

Method used

Fly ash-slag-based regenerated aggregate and sea sand are used as alternative materials, combined with geopolymer concrete technology, slag and fly ash are activated through alkali exciters to form concrete with excellent mechanical properties.

Benefits of technology

It effectively reduces the environmental damage caused by cement firing, alleviates the problem of shortage of river sand resources, and realizes the efficient recycling of waste concrete in construction, with high economic, environmental and social benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490325A_ABST
    Figure CN119490325A_ABST
Patent Text Reader

Abstract

The invention discloses fly ash-slag-based recycled aggregate sea sand geopolymer concrete and a preparation method thereof, and belongs to the technical field of cement-based building materials. The coal ash-slag based recycled aggregate sea sand geopolymer concrete is prepared from the following raw materials: 375.7 kg / m < 3 > of coal ash, 161.1 kg / m < 3 > of slag, 454.4 kg / m < 3 > of sea sand, 529.4 kg / m < 3 > of natural aggregate, 529.4 kg / m < 3 > of recycled aggregate, 245 kg / m < 3 > of alkali activator and 2-5 kg / m < 3 > of retarder. According to the concrete, the characteristics and advantages of materials such as the fly ash, the slag, the recycled aggregate and the sea sand are fully utilized, so that the concrete material has relatively high mechanical properties, working properties and economic and environment-friendly values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, and in particular to a fly ash-slag based recycled aggregate sea sand geopolymer concrete and a preparation method thereof. Background Art

[0002] Urban construction in my country is in full swing. As one of the most important and widely used building materials in the world, concrete is widely used in various engineering constructions in modern society due to its easy pouring, fast molding, abundant raw material sources, low price, mature technology, and strong fire resistance. It will continue to be the most important building structure material for a long time in the future.

[0003] But first of all, the production process of concrete is often accompanied by a large amount of energy consumption and a large amount of carbon dioxide emissions. my country is a major cement producer. In 2020, cement production accounted for 53.84% of global production. The CO2 generated during cement production reached 1.23 billion tons, accounting for 83.11% of China's carbon emissions from the building materials industry. At present, one of the main ways to solve the problem of excessive carbon emissions in the concrete production process is to use new cementitious materials to replace cement to control carbon emissions from the source.

[0004] The second is the issue of construction sand. River sand is a non-renewable resource with a limited total storage capacity. If it is mined continuously, there will always be a day when the sand resources will be exhausted. Excessive exploitation of river sand will also change the bottom surface of the riverbed, thereby changing the hydrological laws of the river, forming a series of problems such as vortexes and backflows. Therefore, it is an extremely urgent issue to find a way to reasonably and safely use sea sand for construction sand before the river sand is exhausted. The total amount of sea sand resources in China's coastal waters is huge. From the perspective of resource development and comprehensive utilization, due to the increasing shortage of river sand, if sea sand can be used to mix concrete, it will be a good way to "turn waste into treasure" for comprehensive resource utilization and sustainable development.

[0005] At the same time, concrete, as the largest consumer of natural resources such as water, sand, pebbles and gravel, is now consuming natural aggregates at a rate of about 8 billion tons per year. At the same time, with the rapid development of urban construction, the improvement of people's material life, the original buildings cannot meet their use requirements and the approaching service life, more and more buildings will be demolished, generating more and more construction waste. The recycled aggregate produced after the treatment of construction waste can be used as a substitute for natural aggregate. Using it as an aggregate can produce lightweight concrete, which can reduce the deadweight of the structure and realize the economic and environmental protection of engineering construction.

[0006] Fly ash, slag and other industrial byproducts produced by thermal power generation, metal smelting and other industrial activities can easily cause soil and water pollution if not properly handled. However, these byproducts have the potential to replace cement as a cementitious material under the action of alkaline or acidic activators. Alkaline activators are used to increase the activity of powders such as slag and fly ash, and then polymerize to form an inorganic cementitious material with a three-dimensional network bonding structure of Si, Al, and O. Compared with ordinary cement, geopolymer concrete has the advantages of low hydration heat, good frost resistance and strong corrosion resistance.

[0007] Geopolymers are used to replace ordinary cement as a cementitious material, sea sand is used to replace river sand, and recycled aggregates from construction waste concrete are used to partially replace natural aggregates to prepare a fly ash-slag-based recycled aggregate sea sand geopolymer concrete. On this basis, a systematic and in-depth study of the material properties and mechanical properties of this green environmentally friendly concrete is carried out. This can not only reduce the environmental damage and pollution caused by cement burning, greatly alleviate the problem of river sand resource shortage, but also effectively realize the resource-based and efficient recycling of waste concrete. Therefore, if fly ash-slag-based recycled aggregate sea sand geopolymer concrete is used to partially or completely replace ordinary concrete, it will greatly alleviate the current environmental deterioration and resource scarcity problems, have high economic benefits, environmental benefits and social benefits, and have broad prospects for engineering applications. Summary of the invention

[0008] In order to solve the problems in the prior art, the present invention provides a fly ash-slag based recycled aggregate sea sand geopolymer concrete and a preparation method thereof.

[0009] Specifically, the fly ash-slag based recycled aggregate sea sand geopolymer concrete of the present invention is composed of the following raw materials in parts by weight: fly ash 375.7 kg / m 3 , slag 161.1kg / m 3 , sea sand 454.4kg / m 3 , natural aggregate 529.4kg / m 3 , recycled aggregate 529.4kg / m 3 , alkali activator 245kg / m 3 , retarder 2~5kg / m 3 .

[0010] Preferably, the fly ash is primary fly ash.

[0011] Preferably, the slag is S95 type slag powder.

[0012] Preferably, the sea sand is undisturbed sea sand from the South China Sea, with a density of 1490 kg / m 3 , fineness modulus is 2.2, shell content is 1%, and chloride ion content is 0.074%.

[0013] Preferably, the particle size of the recycled aggregate is 5 to 20 mm.

[0014] Preferably, the particle size of the recycled aggregate is 5 to 20 mm.

[0015] Preferably, the alkaline activator is composed of 12 mol / L NaOH solution and Na2SiO4 solution, and the mass ratio of the NaOH solution to the Na2SiO4 solution is 1:2.5.

[0016] Preferably, the retarder is one or more of BaCl2, calcium sucrose and sodium gluconate.

[0017] The present invention also provides a method for preparing fly ash-slag based recycled aggregate sea sand geopolymer concrete, comprising the following steps:

[0018] 1) Mix NaOH solution and Na2SiO4 solution in a mass ratio of 1:2.5 in advance for use. First, pour all the natural aggregate and recycled aggregate into the mixer to form the bottom. Then mix the fly ash and slag and pour them into the mixer and stir slowly for 1 minute. Then add sea sand and retarder and stir for another 1 minute to make the dry materials evenly mixed.

[0019] 2) After all materials are mixed evenly, slowly pour in the alkali activator while stirring, stir for 2 minutes, then discharge the material and put it into the mold;

[0020] 3) After entering the mold, place the specimen on a vibration table and vibrate for 1 to 2 minutes until no obvious large bubbles emerge from the surface. Cover the surface of the vibrated specimen with plastic wrap to prevent moisture evaporation and sprinkle water around the mold to maintain a certain humidity. Place it at room temperature for 24 hours, remove the mold, and cure for 7 days and 28 days.

[0021] 4) Pour the mixed slurry into a mold, vibrate it into shape, and seal it with a plastic film. After demoulding, continue to cure it at room temperature for 28 days to obtain fly ash-slag based recycled aggregate sea sand geopolymer concrete.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The recycled geopolymer concrete provided by the present invention fully utilizes the characteristics and advantages of materials such as fly ash, slag, recycled aggregate, and sea sand, so that the concrete material has higher mechanical properties, workability, and economic and environmental value.

[0024] (2) The present invention partially replaces natural aggregate with recycled aggregate and replaces river sand with sea sand, which can reduce the environmental damage caused by cement burning and river sand mining, and responds to the national call for green buildings.

[0025] (5) The recycled geopolymer concrete provided by the present invention has an average compressive strength of up to 43.92 MPa at 7 days and an average compressive strength of up to 61.97 MPa at 28 days. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a technical flow chart of the present invention.

[0027] Figure 2 is the particle size distribution of fly ash particles.

[0028] Figure 3 is the particle size distribution of slag particles. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings:

[0030] To further illustrate the present invention, a fly ash-slag based recycled aggregate sea sand geopolymer concrete and a preparation method provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0031] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.

[0032] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.

[0033] Example 1

[0034] The raw materials prepared in Example 1 are prepared from raw materials containing the following components, measured by unit volume mass: fly ash 375.7 kg / m 3 , slag 161.1kg / m 3 , sea sand 454.4kg / m 3 , natural aggregate 529.4kg / m 3 , recycled aggregate 529.4kg / m 3 , alkali activator 245kg / m 3 , BaCl2 (retarder) 2~5kg / m 3 .

[0035] First, mix the NaOH solution and the Na2SiO4 solution in a mass ratio of 1:2.5 in advance for later use. First, pour all the natural aggregate and recycled aggregate into the mixer to form the bottom. Then mix the fly ash and slag and pour them into the mixer and stir slowly for 1 minute. Then add sea sand and BaCl2 and stir for 1 minute to mix the dry materials evenly. After all the materials are mixed evenly, slowly pour the alkali activator while stirring. After stirring for 2 minutes, discharge the material and put it into the mold. After putting it into the mold, put the specimen on the vibration table and vibrate it for 1 to 2 minutes until no obvious large bubbles emerge from the surface. Cover the surface of the vibrated specimen with plastic wrap to prevent water evaporation and sprinkle water around the mold to maintain a certain humidity. Place it at room temperature for 24 hours, remove the mold, and cure it for 7 days and 28 days to obtain fly ash-slag based recycled aggregate sea sand geopolymer concrete.

[0036] Example 2

[0037] The raw materials prepared in Example 2 are prepared from raw materials containing the following components, measured by unit volume mass: fly ash 375.7 kg / m 3 , slag 161.1kg / m 3 , sea sand 454.4kg / m 3 , natural aggregate 794.1kg / m 3 , recycled aggregate 264.7kg / m 3 , alkali activator 245kg / m 3 , BaCl2 (retarder) 2~5kg / m 3 .

[0038] First, mix the NaOH solution and the Na2SiO4 solution in a mass ratio of 1:2.5 in advance for later use. First, pour all the natural aggregate and recycled aggregate into the mixer to form the bottom. Then mix the fly ash and slag and pour them into the mixer and stir slowly for 1 minute. Then add sea sand and BaCl2 and stir for 1 minute to mix the dry materials evenly. After all the materials are mixed evenly, slowly pour the alkali activator while stirring. After stirring for 2 minutes, discharge the material and put it into the mold. After putting it into the mold, put the specimen on the vibration table and vibrate it for 1 to 2 minutes until no obvious large bubbles emerge from the surface. Cover the surface of the vibrated specimen with plastic wrap to prevent water evaporation and sprinkle water around the mold to maintain a certain humidity. Place it at room temperature for 24 hours, remove the mold, and cure it for 7 days and 28 days to obtain fly ash-slag based recycled aggregate sea sand geopolymer concrete.

[0039] Example 3

[0040] The raw materials prepared in Example 1 are prepared from raw materials containing the following components, measured by unit volume mass: fly ash 375.7 kg / m 3 , slag 161.1kg / m 3 , sea sand 454.4kg / m 3, natural aggregate 264.7kg / m 3 , recycled aggregate 794.1kg / m 3 , alkali activator 245kg / m 3 , BaCl2 (retarder) 2~5kg / m 3 .

[0041] First, mix the NaOH solution and the Na2SiO4 solution in a mass ratio of 1:2.5 in advance for later use. First, pour all the natural aggregate and recycled aggregate into the mixer to form the bottom. Then mix the fly ash and slag and pour them into the mixer and stir slowly for 1 minute. Then add sea sand and BaCl2 and stir for 1 minute to mix the dry materials evenly. After all the materials are mixed evenly, slowly pour the alkali activator while stirring. After stirring for 2 minutes, discharge the material and put it into the mold. After putting it into the mold, put the specimen on the vibration table and vibrate it for 1 to 2 minutes until no obvious large bubbles emerge from the surface. Cover the surface of the vibrated specimen with plastic wrap to prevent water evaporation and sprinkle water around the mold to maintain a certain humidity. Place it at room temperature for 24 hours, remove the mold, and cure it for 7 days and 28 days to obtain fly ash-slag based recycled aggregate sea sand geopolymer concrete.

[0042] Example 4

[0043] The raw materials prepared in Example 4 are prepared from raw materials containing the following components, measured by unit volume mass: fly ash 375.7 kg / m 3 , slag 161.1kg / m 3 , sea sand 454.4kg / m 3 , recycled aggregate 1058.7kg / m 3 , alkali activator 245kg / m 3 , BaCl2 (retarder) 2~5kg / m 3 .

[0044] First, mix the NaOH solution and the Na2SiO4 solution in a mass ratio of 1:2.5 in advance for later use. First, pour all the recycled aggregate into the mixer to form the bottom. Then mix the fly ash and slag and pour them into the mixer and stir slowly for 1 minute. Then add sea sand and BaCl2 and stir for 1 minute to mix the dry materials evenly. After all the materials are mixed evenly, slowly pour the alkali activator while stirring. After stirring for 2 minutes, discharge the material and put it into the mold. After entering the mold, put the specimen on the vibration table and vibrate for 1 to 2 minutes until no obvious large bubbles emerge from the surface. Cover the surface of the vibrated specimen with plastic wrap to prevent water evaporation and sprinkle water around the mold to maintain a certain humidity. Place it at room temperature for 24 hours, remove the mold, and cure for 7 days and 28 days to obtain fly ash-slag based recycled aggregate sea sand geopolymer concrete.

[0045] Table 1 Concrete performance test results

[0046]

[0047] As shown in Table 1, it can be found that the 7d strength of the four groups of specimens is almost the same, the highest strength is 43.92MPa in Example 2, which is only 2.9% different from the lowest strength of 42.64MPa in Example 4. The compressive strength of the other two groups (Example 1 and Example 3) is also between 43.92MPa and 42.67MPa, which can be considered as experimental errors and unchanged. For the 28d strength, it can be seen that at low recycled aggregate replacement rate (0-50%), the compressive strength of the concrete cube remains basically unchanged, and the highest and lowest strengths are 61.97MPa and 60.10MPa, respectively, with a difference of only 3%. When the replacement rate gradually increases to 100%, the compressive strength decreases to 54.80MPa in Example 4, and the highest strength in the 28d compressive strength is 13% higher than the lowest strength. It can be seen that except for the 100% replacement rate, the higher the replacement rate of recycled aggregate, the greater the increase in strength of the specimen from 7d to 28d. This is because with the increase in the replacement rate of recycled aggregate, the water content in the micro-cracks of the aggregate will also increase, which is equivalent to a slight increase in the water-cement ratio, providing more solvent for the alkali-induced hydration reaction, and better stimulating materials rich in silicon and aluminum elements such as slag and fly ash, which not only makes the reaction more intense and complete, but also enhances the cohesiveness between aggregate and mortar, and promotes its later strength development. Therefore, with the increase in the replacement rate of recycled aggregate, the strength improvement of the specimen from 7d to 28d gradually increases. It can be seen that fly ash-slag based recycled aggregate sea sand geopolymer concrete has excellent mechanical properties.

[0048] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0049] In summary, the fly ash-slag based recycled aggregate sea sand geopolymer concrete of the present invention, the shotcrete after adding polypropylene fiber, cellulose fiber and anti-seepage enhancer has the characteristics of low porosity and high density, good anti-seepage performance, good resistance to groundwater erosion of lining, and provides a rich safety reserve for safe operation of tunnels. The fly ash-slag based recycled aggregate sea sand geopolymer concrete of the present invention not only has a good seepage and anti-crystallization effect in the early stage, but the subsequent seepage process will make more anti-seepage enhancers play a role, and the shotcrete is more dense, which serves the purpose of resisting long-term seepage crystallization. For water-rich tunnels in limestone areas, especially water-rich tunnels with corrosive groundwater, it can effectively prevent the seepage crystallization problem of shotcrete in the initial support of the tunnel, and further ensure the safety of the tunnel structure and the smooth operation of the drainage system.

Claims

1. A fly ash-slag based recycled aggregate sea sand geopolymer concrete, characterized in that: The raw materials are composed of the following components: fly ash 375.7 kg / m 3 , slag 161.1kg / m 3 , sea sand 454.4kg / m 3 , natural aggregate 529.4kg / m 3 , recycled aggregate 529.4kg / m 3 , alkali activator 245kg / m 3 , retarder 2~5kg / m 3 .

2. The fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The fly ash is first-grade fly ash.

3. The fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The slag is S95 type slag powder.

4. The fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The sea sand is the original sea sand from the South China Sea, with a density of 1490 kg / m 3 , fineness modulus is 2.2, shell content is 1%, and chloride ion content is 0.074%.

5. The fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The particle size of the natural aggregate is 5 to 20 mm.

6. The fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The particle size of the recycled aggregate is 5 to 20 mm.

7. The fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The alkaline activator is composed of 12 mol / L NaOH solution and Na2SiO4 solution.

8. The fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The mass ratio of the NaOH solution to the Na2SiO4 solution in the alkaline activator is 1:2.

5.

9. The fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The retarder is one or more of BaCl2, calcium sucrose and sodium gluconate.

10. The method for preparing the fly ash-slag based recycled aggregate sea sand geopolymer concrete according to claim 1, characterized in that: The steps include: 1) Mix NaOH solution and Na2SiO4 solution in a mass ratio of 1:2.5 in advance for use. First, pour all the natural aggregate and recycled aggregate into the mixer to form the bottom. Then mix the fly ash and slag and pour them into the mixer and stir slowly for 1 minute. Then add sea sand and retarder and stir for another 1 minute to make the dry materials evenly mixed. 2) After all materials are mixed evenly, slowly pour in the alkali activator while stirring, stir for 2 minutes, then discharge the material and put it into the mold; 3) After entering the mold, place the specimen on a vibration table and vibrate for 1 to 2 minutes until no obvious large bubbles emerge from the surface. Cover the surface of the vibrated specimen with plastic wrap to prevent moisture evaporation and sprinkle water around the mold to maintain a certain humidity. Place it at room temperature for 24 hours, remove the mold, and cure for 7 days and 28 days. 4) Pour the mixed slurry into a mold, vibrate it into shape, and seal it with a plastic film. After demoulding, continue to cure it at room temperature for 28 days to obtain fly ash-slag based recycled aggregate sea sand geopolymer concrete.